2013
DOI: 10.1021/ja3122312
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cell Death by Photochemically Induced pH Imbalance in Cancer Cells

Abstract: Singlet oxygen sensitized photodynamic therapy (PDT) relies on the concentration of oxygen in the tissue to be treated. Most cancer lesions, however, have poor vasculature and, as a result, are hypoxic, significantly hindering PDT efficacies. An oxygen-independent PDT method may circumvent this limitation. To address this, we prepared sulfonium salts that produced a pH drop within HCT 116 cells via the generation of photoacid within the cytosol. This process was driven by one- or two-photon absorption (1PA or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 22 publications
(27 reference statements)
1
67
1
1
Order By: Relevance
“…Fadhel et al As demonstrated in our previous study, 6 time-lapsed micrographs ( Figure 6) of HCT-116 cells incubated with PEG-PAG9 and SiNP-PAG9 (Figures 6 and 7, respectively) show significant cell swelling, loss of cell adhesion that is followed by a "blebbing"-like activity, which is a characteristic of necrotic cell death. Figure 8 shows a simplified Jablonski diagram summarizing the process of photoacid generation by either one-photon or two-photon (2P) excitation.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Fadhel et al As demonstrated in our previous study, 6 time-lapsed micrographs ( Figure 6) of HCT-116 cells incubated with PEG-PAG9 and SiNP-PAG9 (Figures 6 and 7, respectively) show significant cell swelling, loss of cell adhesion that is followed by a "blebbing"-like activity, which is a characteristic of necrotic cell death. Figure 8 shows a simplified Jablonski diagram summarizing the process of photoacid generation by either one-photon or two-photon (2P) excitation.…”
supporting
confidence: 68%
“…Next, we verified the reduced lysosomal pH by employing LysoSensor Green as a suitable intracellular pH sensor. 6 Since the fluorescence quantum yield of LysoSensor Green increases in increasingly acidic environments, 11 International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 54.245.13.81 on 11-May-2018 For personal use only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiphotonics has gained increasing popularity in the life sciences over the last decade, in relation with the many advantages molecular multiphoton absorption [1][2][3][4] provides for biological or biomedical applications, such as multiphoton excited fluorescence imaging, [5][6][7] and photodynamic therapy (PDT), [8][9][10][11][12][13][14] . The advantages of two-photon absorption (2PA) M a n u s c r i p t 2 include the ability for highly selective excitation in biological media, intrinsic threedimensional resolution as well as increased penetration depth in tissues.…”
Section: Introductionmentioning
confidence: 99%